1986
DOI: 10.1111/j.1440-1827.1986.tb02837.x
|View full text |Cite
|
Sign up to set email alerts
|

A LIGHT AND ELECTRON MICROSCOPIC STUDY OF THE REGENERATIVE EPITHELIUM IN THE INTRAHEPATIC BILE DUCT: Experimental Study of Local Direct Instillation of Paraquat Into the Intrahepatic Bile Ducts of Rats

Abstract: To date, no reliable report on the regeneration of the intrahepatic bile duct epithelium following damage to the duct has been published. In this study, a direct instillation of paraquat dichloride into the intrahepatic bile ducts of rats was carried out, and the livers were examined under light and electron microscopy. One hour after treatment, the biliary epithelia showed degeneration and necrosis, and these changes remained for a considerable period in a large majority of the ducts examined.Three weeks afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Then we used N -butyl-cyanoacrylate (tissue adhesive glue) to further destroy biliary mucosa, prevent mucosal regeneration and permanently fill the diseased biliary duct lumen. 18,20 As expected, the HE staining and in situ hybridization for collagen I showed that the mucosa of the embolized biliary duct was completely destroyed and almost entirely replaced by collagen fiber. As a result, CPC and its stone-forming potential were effectively eradicated.…”
Section: Discussionmentioning
confidence: 56%
“…Then we used N -butyl-cyanoacrylate (tissue adhesive glue) to further destroy biliary mucosa, prevent mucosal regeneration and permanently fill the diseased biliary duct lumen. 18,20 As expected, the HE staining and in situ hybridization for collagen I showed that the mucosa of the embolized biliary duct was completely destroyed and almost entirely replaced by collagen fiber. As a result, CPC and its stone-forming potential were effectively eradicated.…”
Section: Discussionmentioning
confidence: 56%
“…However, the biliary system could not be permanently occluded by using phenol or ethanol alone, due to the regeneration of biliary mucosa 10,14 . Thus, we chose cyanoacrylate, a tissue adhesive glue, to further embolize biliary ducts, destroy biliary mucosa and prevent mucous regeneration 12,15 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the biliary system could not be permanently occluded by using phenol or ethanol alone, due to the regeneration of biliary mucosa. 10,14 Thus, we chose cyanoacrylate, a tissue adhesive glue, to further embolize biliary ducts, destroy biliary mucosa and prevent mucous regeneration. 12,15 Our histological observation demonstrated that cyanoacrylate could fill bile ducts of various sizes (including the acroteric branch), and thus lead to the complete disappearance of mucosal epithelia which were entirely replaced by foreign-body granuloma and collagen fiber.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of BECs can be confirmed using in situ nick-end labelling and immunostaining of single stranded DNA, both of which detect DNA fragmentation. In contrast, the coagulative or lytic necrosis of the biliary epithelium is occasionally encountered in toxic cholangiopathy [18]. …”
Section: Basic Injuries Of Biliary Epithelial Cells and Bile Duct mentioning
confidence: 99%
“…Ischemic changes to the peribiliary vascular plexus may be at least partly involved in this type of cholangiopathy. Although BECs have low metabolic activity compared with hepatocytes, cytotoxic or cytopathic bile duct injury has been produced experimentally or accidentally by toxic substances such as α -naphthylisothiocyanate, 4,4′-diaminodiphenylmethane, and paraquat (toxin-induced cholangiopathy) [18]. …”
Section: Cholangiopathiesmentioning
confidence: 99%